Efektivitas Project-Based Learning dalam Meningkatkan Pemahaman Fiqih pada Materi Zakat Fitrah dan Mal - Antoni, Putri Alfianah; Wulandari, Maulidiyah Nur; Rohmad, Muhammad Ali (PTK: Jurnal Tindakan Kelas, 2025)
This research aims to evaluate the effectiveness of the Project-Based Learning method in increasing the understanding of class X students at Madrasah Aliyah Darul Hikam Mojokerto regarding zakat fitrah and zakat mal. This qualitative descriptive research used the Classroom Action Research (PTK) method which was carried out in two cycles. Data was collected through pre-test, post-test, semi-structured interviews, and observation. The results showed a significant increase in students' understanding, with the average score increasing from 58.28 (pre-test) to 90.71 (post-test) (p < 0.05). Interviews revealed that PjBL not only increases student motivation and engagement, but also bridges the gap between theory and the practical application of jurisprudence. Obstacles such as limited time and variations in students' initial abilities are challenges that need to be overcome. This research concludes that PjBL is an effective method for increasing understanding of fiqh material, as well as providing recommendations for digital technology integration for future optimization.